(untitled) (Bangladesh Journal of Zoology, 2018)
Present study was conducted to evaluate nutritional values of smoked hilsa fish (Tenualosa ilisha; Hamilton, 1882) in relation to its raw condition. Smoking is one of the processes of fish preservation from ancient period of our country. The nutrients values of the hilsa from two different regions were significantly (p < 0.05) varied. The nutritional values were different before and after processing of hilsa. Riverine hilsa contains relatively more moisture (56.45 ± 0.51%) and protein (15.98 ± 0.50%) than marine hilsa. Fat (16.18 ± 0.45%) and salt (1.92 ± 0.18%) contents are higher in marine hilsa; whereas ash (8.34 ± 0.35%) content was higher in riverine hilsa. Minerals like iron (4.72 ± 0.08 mg/100 g) and calcium (481.77 ± 6.20 mg/100g) remain in large amount on marine hilsa but phosphorus (115.73 ± 4.36 mg/100 g) content remain high level in riverine hilsa. In addition, the protein (raw condition, 19.54 ± 0.47%, riverine; 17.12 ± 0.42%, marine and smoked condition, 29.64 ± 0.41%, riverine; 28.51 ± 0.51%, marine) and fat (raw condition, 16.41 ± 0.46%, riverine; 20.07 ± 0.39%, marine and smoked condition, 20.71 ± 0.47%, riverine; 23.31 ± 0.47%, marine) content were higher in abdominal region of riverine and marine hilsa both raw and smoked condition than head region (protein in raw condition, 11.21 ± 0.51%, riverine; 10.51 ± 0.53%, marine and smoked condition, 17.14 ± 0.42%, riverine; 15.69 ± 0.4%, marine; fat in raw condition, 9.04 ± 0.45%, riverine; 11.21 ± 0.51%, marine and smoked condition, 12.32 ± 0.44%, riverine; 14.56 ± 0.47%, marine) and caudal region (protein in raw condition17.21 ± 0.52%, riverine; 15.22 ± 0.66%, marine and smoked condition, 27.68 ± 0.44%, riverine; 26.73 ± 0.46%, marine; fat in raw condition, 14.05 ± 0.5%, riverine; 17.28 ± 0.47%, marine and smoked condition, 17.35 ± 0.43%, riverine; 19.18 ± 0.51%, marine). Bangladesh J. Zool. 46(2): 177-184, 2018